2022
DOI: 10.1037/tra0001056
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on gender-based violence in the United States: Framework and policy recommendations.

Abstract: Objective: In response to the 2019 novel coronavirus pandemic, portions of the U.S. government implemented social distancing policies that, while necessary, yield unintended consequences. This article explores how risk for gender-based violence (GBV) has been exacerbated across the social-ecological model (SEM; e.g., by increasing economic stress and decreasing social support) and highlights differential impact across social locations (e.g., considering race, gender, social class). Method: Drawing on gender-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 82 publications
1
27
0
1
Order By: Relevance
“…As our data were derived from an anonymous, confidential hotline which does not directly solicit information from users, we were also unable to collect demographic data points, although we know that the pandemic impacted communities differently ( Rieger et al, 2022 ). Early findings suggest that demographic factors such as race and ethnicity affect vulnerability to COVID-19-related difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…As our data were derived from an anonymous, confidential hotline which does not directly solicit information from users, we were also unable to collect demographic data points, although we know that the pandemic impacted communities differently ( Rieger et al, 2022 ). Early findings suggest that demographic factors such as race and ethnicity affect vulnerability to COVID-19-related difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Social psychology GBV research has focused on the complex interplay between individual, relationship, community, and societal factors that place people at risk or protect them from violence (e.g., Anderson & Anderson, 2008 ; Hollomotz, 2009 ). For example, Rieger et al (2021) recently explored this interplay within the context of intersectionality, defined as the holding of multiple and intersecting identities (e.g., Latina lesbian youth ), and GBV. Their work concluded that effective GBV efforts must be tailored to address structural inequalities and include prioritization of resources and opportunities (e.g., economic, educational), especially for those with intersecting identities who are at increased risk.…”
Section: Psychological Approachesmentioning
confidence: 99%
“…The heightened risk of gender-based violence during a pandemic in all communities is well documented (Dlamini, 2020; Johnson et al, 2020; Mittal & Singh, 2020; Rieger et al, 2021; Sharma & Borah, 2020), and college and university communities are no exception (Barlow, 2020). The financial challenges and isolation imposed by the COVID-19 pandemic resulted in situations that were less than ideal and, in some cases, unsafe for students and employees.…”
Section: Campus Sv Prevention and Response In A Pandemicmentioning
confidence: 99%
“…In the early months of the pandemic, campus practitioners, researchers, and allies raised alarm that colleges may “abandon” their commitment to SV prevention, despite the increases in violence related to the pandemic (Dlamini, 2020; Johnson et al, 2020; Mittal & Singh, 2020; Rieger et al, 2021; Sharma & Borah, 2020). Campus practitioners also noted the challenges of reaching and supporting SV survivors during this time (Bennett et al, 2021).…”
Section: Campus Sv Prevention and Response In A Pandemicmentioning
confidence: 99%